Immunological studies on brucellosis with special reference to the use of S.19 vaccine in cattle - McDiarmid, Archibald (The University of Edinburgh, 1953)
1. Immunity in Cattle Vaccinated with Brucella Abortus Strain 19 and a Note Comparing this Strain with 45/20. • 2. The Transference of Agglutinins for Brucella Abortus from Cow to Calf and their Persistence in the Calf's Blood. • 3. An Observation on Reduction in Milk Yield following Vaccination Of Lactating Cows with Living Vaccines prepared from Brucella Abortus. • 4.. A Comparison of the Immunity produced in :Guinea Pigs by the Inoculation of S.19 Br. abortus Vaccine Intradermally and Subcutaneously. • 5. A Comparison of the Imsunisin: Value in Cattle of Dead Antigens and 5.19 Br. abortus Vaccine. • 6. The Stability of the Avirulent Characters of Brucella abortus strain 19 and strain 45/20 in Lactating and Pregnant Cows. • 7. A Comparison of the Immunity produced in Cattle by the Inoculation of Br. abortus strain 19 Intradermally, Intracaudally and Subcutaneously. • 8. The Jccurrence of Vibrio foetus in Aborted Idaterial derived from Cows inoculated with S.19 Br. abortus Vaccine. • 9. The Vaccination of Pregnant Cattle with strain. 19 Br. abortus Vaccine during an Outbreak of Brucellosis in a Dairy Herd. • 10. The Occurrence of Agglutinins for Br. abortus in the Blood of Wild Deer in the South of England. • 11. A Comparison of the Intradermal and Subcutaneous Routes in producing Immunity to Brucellosis in Cattle. • 12. Assessing the immunising Value of Br. abortus Vaccines in Cattle.

The following thesis consists of twelve papers recording the results of an investigation concerning various aspects of brucellosis. With one exception all have been published, and this paper has now also been accepted for publication.

The work described has proceeded over a period, of tell years from 1943 to 1953 at the Agricultural Research Council's Field Station, Compton, Berkshire, the main object being; the furtherance of knowledge pertaining to the immunisation of cattle against brucellosis. The technique of experimentation in cattle on a scale calculated to be sufficiently large to provide reliable results has been developed, particular attention being directed towards ensuring that the previous relevant history of the experimental animals was known. Special isolation precautions have been evolved to ensure that no extraneous infection could gain access to the animals during the experimental period and, to enable comparisons to be made between different immunising antigens, a standardised method of infecting the experimental cattle with brucellosis has now been established. Much of the information so far obtained, has already been utilised by the Ministry of Agriculture and Public Health authorities in this and other countries to assist in formulating policies designed to prevent the occurrence of brucellosis in cattle and in man. It was inevitable that certain results had to be published in conjunction with one or more colleagues because this field of research was too vast for any one individual to cover alone. Accordingly, in order to maintain continuity, these four additional papers have been incorporated in the text in sequence, rather than in an appendix. In these conjoint experiments the present author has been wholly responsible for all aspects of the work directly concerning the experimental cattle and in addition has performed all the serological and many of the cultural and biological tests.